Concentrations of pyridinoline and deoxypyridinoline in joint tissues from patients with osteoarthritis or rheumatoid arthritis. Issue 5 (May 1996) - Takahashi, M; Kushida, K; Hoshino, H; Suzuki, M; Sano, M; Miyamoto, S; Inoue, T
Abstract : OBJECTIVE: To assess the usefulness of pyridinoline (Pyr) and deoxypyridinoline (Dpyr), intermolecular crosslinks of collagen, as markers in the evaluation of arthritis, by studying their distribution in tissues from knee joints. METHODS: Joint tissues (cartilage, bone, synovium) were obtained during operation from 10 patients with osteoarthritis (OA) and 10 patients with rheumatoid arthritis (RA). Synovium was also obtained from 10 non-arthritic (NA) subjects. Hydroxyproline was measured in hydrolysed tissue samples and converted to an equivalent collagen content. The amounts of Pyr and Dpyr crosslinks measured in the hydrolysed samples using a fluorescence technique were expressed as mumol/mol of collagen. RESULTS: Pyr and Dpyr were distributed in all three tissues, but in different amounts. The ratio of the contents of Pyr and (Pyr:Dpyr) was 50:1 in cartilage, 3:1 in bone, and 25:1 in synovium. OA cartilage had a greater Dpyr content than the RA cartilage, but there was no other significant difference in the contents of Pyr and Dpyr and the ratio Pyr:Dpyr in the joint tissues from patients with OA or RA. In synovium, there was no significant difference between the contents of Pyr and Dpyr and the Pyr:Dpyr ratio among OA, RA, and NA tissues. CONCLUSION: Both Pyr and Dpyr were located in cartilage, bone, and synovium. A significant amount of Pyr and Dpyr in these joint tissues, especially in synovium, may contribute to the urinary excretion of those crosslinks that is observed in arthritis.